2016
DOI: 10.1186/s12870-016-0887-0
|View full text |Cite
|
Sign up to set email alerts
|

Cell wall dynamics during apple development and storage involves hemicellulose modifications and related expressed genes

Abstract: BackgroundFruit quality depends on a series of biochemical events that modify appearance, flavour and texture throughout fruit development and ripening. Cell wall polysaccharide remodelling largely contributes to the elaboration of fleshy fruit texture. Although several genes and enzymes involved in cell wall polysaccharide biosynthesis and modifications are known, their coordinated activity in these processes is yet to be discovered.ResultsCombined transcriptomic and biochemical analyses allowed the identific… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
36
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 65 publications
(45 citation statements)
references
References 129 publications
(179 reference statements)
7
36
0
Order By: Relevance
“…Our research also revealed the presence of de-methylesterified (DME), partially DME and fully methyl-esterified (ME) pectin residues in the cell walls and middle lamella of stele and cortical tissues involved in aerenchyma formation. Previous research proposed that removal of methyl ester substitutions from the homogalacturonan domains of pectin enables degradation of cell walls by unblocking cleavage sites between pectin residues, which are then targeted by polygalacturonases, pectin lyases and similar hydrolytic enzymes (Dheilly et al, 2016). Our observations showed that DME pectin is spatially localized within one to three cell layers around aerenchyma and increases from partial and fully DME during aerenchyma development (Figures 4-7).…”
Section: Discussionsupporting
confidence: 54%
“…Our research also revealed the presence of de-methylesterified (DME), partially DME and fully methyl-esterified (ME) pectin residues in the cell walls and middle lamella of stele and cortical tissues involved in aerenchyma formation. Previous research proposed that removal of methyl ester substitutions from the homogalacturonan domains of pectin enables degradation of cell walls by unblocking cleavage sites between pectin residues, which are then targeted by polygalacturonases, pectin lyases and similar hydrolytic enzymes (Dheilly et al, 2016). Our observations showed that DME pectin is spatially localized within one to three cell layers around aerenchyma and increases from partial and fully DME during aerenchyma development (Figures 4-7).…”
Section: Discussionsupporting
confidence: 54%
“…Mannose is known as a component of the plant cell wall, specifically hemicellulose [47]. The previous report mentioned that the concentration of mannose was decreased during fruit development, hence support our findings shown in Figure 6b [48]. Similar to mannose, decrease level of aspartic acid in the pineapple ripening process were also reported during ripening of banana [49].…”
Section: Discussionsupporting
confidence: 90%
“…Both antisense (AS) and sense (S) probes were designed for each sample, and 16.5% of the significantly expressed probes corresponded to antisense (AS) transcripts (Supplementary Table 5). Previous studies (Dheilly et al, 2016) demonstrated that AS transcripts were likely to be involved in small interfering RNA (siRNA), dependent on the negative regulation of the coding mRNAs. Subsequently, this current study considers only the genes with sense (S) probes as differentially expressed transcripts.…”
Section: Microarray Analysismentioning
confidence: 99%